The Impact of Stock Split on the Performance in Indonesian Manufacturing Companies - yustisia, natali (Binus Business Review, 2018)
The purpose of this research was to analyze whether the stock split had an impact on liquidity and return stock in 18 manufacturing companies listed on the Indonesia Stock Exchange (BEI) from 2012 to 2015. The stock performance used in this research was trading volume activity, bid-ask spread, and abnormal return in five days before and five days after the stock split. Data analysis method used was quantitative method by using SPSS 21 with the Kolmogorov-Smirnov normality test, paired sample t-test, and Wilcoxon test. The findings indicate that stock split does not affect the trading volume activity, bid-ask spread, and abnormal return.